Customer value drivers in business markets: Perceptions by purchasing professionals - SYTNIKOV, EVGENI (2009)
Customer value is a complex phenomenon, which has been researched from various perspectives. Although many studies have suggested different sets of values, few papers presented structured models of customer value drivers. This research identifies value drivers based on data gathered during semi-structured interviews with purchasing professionals employed in the printing industry in Russia. Interview data is used to develop a set of value drivers structured from low to high importance as perceived by respondents. Previous research in the domain of trust is used to identify common values that act as antecedents to trust and perceived important by buyers at the same time. Thus a conceptual value-trust framework is suggested. The findings generally support previous research in the field. Three value drivers were identified as being both important as perceived by buyers and conducive to trust – personal relations, technical expertise and corporate reputation. It is suggested that sellers shall invest resources into these three domains to develop long-term trustful relationships with their customers.